The effect of learning implementation of kitab Akhlak lil Banin on the religious character - Imandita, Anisa Nur; Julehah, Julehah; Apriyani, Lena; Apriliani, Salsa; Rosadi, Umar (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study was to determine the effect of learning the book of Akhlaq lil banin volume II on the religious character of class VIII students of MTs Nurul Iman. The approach used in this study is a quantitative approach. This research was conducted at MTs Nurul Iman Bandung. The dominant subjects in this study were class VIII students who studied the book of Akhlaq lil banin volume II, however, to obtain accurate data, discussions with other subjects such as teachers, especially subject teachers, were also needed. The population was 55 students and the research sample was obtained using random sampling techniques. Data were collected through interview, observation methods and questionnaire. Data analysis was carried out using quantitative descriptive analysis and inferential statistical analysis. The results of this study indicate that the implementation of learning the book of akhlaq lil banin volume II has a significant influence on students' religious character. It can be concluded that the more often students learn about the book of akhlaq lil banin volume II, the more it will improve students' religious character.